2012
DOI: 10.4238/2012.august.24.7
|View full text |Cite
|
Sign up to set email alerts
|

Monosomic and molecular mapping of adult plant leaf rust resistance genes in the Brazilian wheat cultivar Toropi

Abstract: ABSTRACT. Leaf rust is one of the most destructive diseases affecting wheat worldwide. The most effective way to control it is to use resistant cultivars. Resistance based on slow-rusting adult plant resistance (APR) genes has proven to be the best method for developing cultivars with durable resistance. A source of slow-rusting APR for leaf rust is the Brazilian wheat cultivar Toropi. The Toropi/IAC 13 F 2 and F 7 recombinant inbred lines (RILs) were developed in previous studies. Phenotypic analysis of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…which belong to an elite group of crops with huge genomic resources to conduct genetic studies and employ molecular breeding. Although several studies have reported QTLs for resistance to rust in wheat (Da-Silva et al 2012; Zhang et al 2013), maize (Collins et al 1999; Kerns et al 1999; Brown et al 2001), sorghum (Tao et al 1998; Peng et al 1999), barley (van Berloo et al 2001), soybean (Hyten et al 2007, 2009), sunflower (Qi et al 2012; Bulos et al 2013), pea (Rai et al 2011), flax (Bo et al 2002), and oat (Zhu and Kaeppler 2003; Portyanko et al 2005; McCartney et al 2011), molecular breeding for rust resistance has been reported in only some cases. For instance, simple marker-assisted selection has been done to check the efficiency of linked markers in improving rust resistance in sunflower (Lawson et al 1998) and wheat (Bariana et al 2007; Mago et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…which belong to an elite group of crops with huge genomic resources to conduct genetic studies and employ molecular breeding. Although several studies have reported QTLs for resistance to rust in wheat (Da-Silva et al 2012; Zhang et al 2013), maize (Collins et al 1999; Kerns et al 1999; Brown et al 2001), sorghum (Tao et al 1998; Peng et al 1999), barley (van Berloo et al 2001), soybean (Hyten et al 2007, 2009), sunflower (Qi et al 2012; Bulos et al 2013), pea (Rai et al 2011), flax (Bo et al 2002), and oat (Zhu and Kaeppler 2003; Portyanko et al 2005; McCartney et al 2011), molecular breeding for rust resistance has been reported in only some cases. For instance, simple marker-assisted selection has been done to check the efficiency of linked markers in improving rust resistance in sunflower (Lawson et al 1998) and wheat (Bariana et al 2007; Mago et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These genes include Lr12 (McIntosh and Baker 1966), Lr13 (Dyck et al 1966), Lr22a and b (Dyck 1979), Lr34 (Dyck 1987), Lr35 (Kerber and Dyck 1990), Lr37 (Bariana and McIntosh 1993), Lr46 (Singh et al 1998), Lr67 (Herrera-Foessel et al 2011; Hiebert et al 2010), Lr68 (Herrera-Foessel et al 2012) and more recently trp - 1 and trp - 2 (Da-Silva et al 2012). Genes Lr34 , Lr46 and Lr67 provide partial or slow resistance to leaf rust and are considered more durable than seedling resistance genes (Caldwell 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Lr53 [68], Lr54 [69], and Lr56 [161] have been recorded in spring wheat cultivars from Chinese origin and are closely linked with Yr35, Yr37, and Yr38, respectively, and Lr62 [162] was recorded in California wheat cultivars linked with the stripe rust resistance gene Yr42. The adult-plant leaf rust resistance genes Lr34, Lr46, Lr67 and Lr68 have been identified in the Brazilian wheat cultivar Toropi [39].…”
Section: Distribution Of Lr Genes In Global Wheat Cultivarsmentioning
confidence: 99%